Distribution and prognostic impact of microglia/macrophage subpopulations in gliomas. (15th January 2019) - Zeiner, Pia S.; Preusse, Corinna; Golebiewska, Anna; Zinke, Jenny; Iriondo, Ane; Muller, Arnaud; Kaoma, Tony; Filipski, Katharina; Müller‐Eschner, Monika; Bernatz, Simon; Blank, Anna‐Eva; Baumgarten, Peter; et al.
Abstract: While the central nervous system is considered an immunoprivileged site and brain tumors display immunosuppressive features, both innate and adaptive immune responses affect glioblastoma (GBM) growth and treatment resistance. However, the impact of the major immune cell population in gliomas, represented by glioma‐associated microglia/macrophages (GAMs), on patients' clinical course is still unclear. Thus, we aimed at assessing the immunohistochemical expression of selected microglia and macrophage markers in 344 gliomas (including gliomas from WHO grade I–IV). Furthermore, we analyzed a cohort of 241 IDH1R132H‐non‐mutant GBM patients for association of GAM subtypes and patient overall survival. Phenotypical properties of GAMs, isolated from high‐grade astrocytomas by CD11b‐based magnetic cell sorting, were analyzed by immunocytochemistry, mRNA microarray, qRT‐PCR and bioinformatic analyses. A higher amount of CD68‐, CD163‐ and CD206‐positive GAMs in the vital tumor core was associated with beneficial patient survival. The mRNA expression profile of GAMs displayed an upregulation of factors that are considered as pro‐inflammatory M1 (eg, CCL2, CCL3L3, CCL4, PTGS2 ) and anti‐inflammatory M2 polarization markers (eg, MRC1, LGMN, CD163, IL10, MSR1 ), the latter rather being associated with phagocytic functions in the GBM microenvironment. In summary, we present evidence that human GBMs contain mixed M1/M2‐like polarized GAMs and that the levels of different GAM subpopulations in the tumor core are positively associated with overall survival of patients with IDH1R132H‐non‐mutant GBMs.